A novel mutation in alpha sarcoglycan gene in an Iranian family with limb girdle muscular dystrophy 2D. (3rd March 2016) - Mojbafan, Marzieh; Nilipour, Yalda; Tonekaboni, Seyed Hasan; Tavakkoly-Bazzaz, Javad; Zeinali, Sirous
Abstract : Objective and importance: The sarcoglycanopathies (SGPs) are a subgroup of autosomal recessive limb girdle muscular dystrophies. They are caused by mutations in gamma, alpha, beta, and delta sarcoglycans (SGs) genes. Alpha-SGPs are the most frequent form of SGPs. Muscle biopsy studies in patients with SGPs have indicated that loss of one SG subunit leads to instability of whole SG complex. Autozygosity mapping is a powerful gene mapping approach for rare recessive inherited disorders in consanguineous families. Clinical presentation: In the present study, proband was a 9 year old girl from consanguineous parents. She was diagnosed at the age of 5 when she had problems climbing stairs. Her creatine kinase level was 16428 U/L. Proximal weakness and ankle contracture were also observed in the patient. Techniques : Autozygosity mapping, using short tandem repeat (STR) markers linked to the SG genes, showed co-segregation of the phenotype with STR markers linked to the SGCA (Alpha-sarcoglycan) gene. Her muscle biopsy also suggested alpha sarcoglycanopathy. Mutation analyses revealed a novel homozygous deletion of 11 base pairs in exon 4 of this gene. This deletion introduces a premature termination codon after the 4th amino acid. This will eliminate the expression of the downstream part of the extracellular domain of the protein. This domain has a critical role by associating with other molecules of dystrophin–glycoprotein complexes. Conclusion : IHC (Immunohistochemistry) studies combined with autozygosity mapping and mutation screening is an efficient diagnostic method in the SGPs.